2020
DOI: 10.1039/c9sc06424a
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Au4Ru2(PPh3)2(SC2H4Ph)8 cluster for light-driven dinitrogen fixation

Abstract: A molecular-like Au4Ru2 cluster supported on TiO2 with oxygen vacancies enables light harvesting to drive the fixation of N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…X-ray crystallography analysis shows that the parent Au 44 (DMBT) 28 nanocluster is composed of an Au 26 kernel, six Au 2 (SR) 3 and two Au(SR) 2 staples (Fig. 1a and1c; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray crystallography analysis shows that the parent Au 44 (DMBT) 28 nanocluster is composed of an Au 26 kernel, six Au 2 (SR) 3 and two Au(SR) 2 staples (Fig. 1a and1c; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The atomically precise metal nanoparticles (often called nanoclusters) bring unprecedented opportunities in signalling clear directions to exploit the cooperativity between the two metal elements within a single nanocluster. 3 Thiolate-protected gold nanoclusters, Au n (SR) m , where n is the number of gold atoms and m is the number of the thiolate ligand SR, have gained momentum over the past years as an exciting area and opened up new horizons in precise tailoring of the composition and structure to control the physicochemical properties. [4][5][6][7][8][9][10][11][12] The Au n (SR) m nanoclusters are typically configured with an inner gold core (or kernel) and various surface motifs, in which the motifs containing both gold and thiolate resemble the staples.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that stabilizing ligands has little effect on the photocatalytic performance. [ 400 ]…”
Section: Application In Catalysismentioning
confidence: 99%
“…15 Doping other metals into the parent nanoclusters is of paramount importance to attain atomically precise bimetal nanoclusters and to use them as well-dened materials for various applications, in particular, catalytic applications. [16][17][18][19][20] The monoplatinum-doped PtAu 24 (SR) 18 nanocluster as a heterogeneous catalyst exhibited higher activity than Au 25 (SR) 18 for the styrene oxidation. 16 Au 47 Cd 2 (TBBT) 31 from Au 44 (TBBT) 28 (TBBT ¼ 4-tert-butylbenzenethiol) doped with Cd atoms into the surface as an electrocatalyst gave rise to very high faradaic efficiencies for CO 2 electroreduction.…”
Section: Introductionmentioning
confidence: 99%
“… 17 The gold nanocluster doped with Ru atoms as a photocatalyst showed an excellent photocatalytic performance for N 2 reduction. 18 Therefore, the doped metal nanoclusters have emerged as a new class of promising catalysts for widely catalysis fields.…”
Section: Introductionmentioning
confidence: 99%